In Situ Synthesis of Carbon Nanotube–Steel Slag Composite for Pb(II) and Cu(II) Removal from Aqueous Solution - Pengfei Yang; Fangxian Li; Beihan Wang; Yanfei Niu; Jiangxiong Wei; Qijun Yu (Nanomaterials, 2022)
Methods and materials that effectively remove heavy metals, such as lead and copper, from wastewater are urgently needed. In this study, steel slag, a low-cost byproduct of steel manufacturing, was utilized as a substrate material for carbon nanotube (CNT) growth by chemical vapor deposition (CVD) to produce a new kind of efficient and low-cost absorbent without any pretreatment. The synthesis parameters of the developed CNT–steel slag composite (SS@CNTs) were optimized, and its adsorption capacities for Pb(II) and Cu(II) were evaluated. The results showed that the optimal growth time, synthesis temperature and acetylene flow rate were 45 min, 600 °C and 200 sccm (standard cubic centimeter per minute), respectively. The SS@CNTs composite had a high adsorption capacity with a maximum removal amount of 427.26 mg·g−1 for Pb(II) and 132.79 mg·g−1 for Cu(II). The adsorption proceeded rapidly during the first 15 min of adsorption and reached equilibrium at approximately 90 min. The adsorption processes were in accordance with the isotherms of the Langmuir model and the pseudo-second-order model, while the adsorption thermodynamics results indicated that the removal for both metals was an endothermic and spontaneous process. This study showed that compared with other adsorbent materials, the SS@CNTs composite is an efficient and low-cost adsorbent for heavy metals such as lead and copper.